Pulmonary outflow tract obstruction in fetuses with complex congenital heart disease: predicting the need for neonatal intervention. (5th December 2012) - Quartermain, M. D.; Glatz, A. C.; Goldberg, D. J.; Cohen, M. S.; Elias, M. D.; Tian, Z.; Rychik, J.
ABSTRACT: Objective: To identify prenatal echocardiographic markers that could predict the need for neonatal intervention in fetuses with right ventricular outflow tract obstruction. Methods: This was a retrospective study of 52 fetuses with right ventricular outflow tract obstruction. Echocardiograms were evaluated for fetuses with either two‐ventricle anatomy with a large ventricular septal defect or single‐ventricle anatomy. Fetuses with pulmonary atresia were excluded. Parameters were compared between groups that did and did not require an intervention at age < 30 days. Results: Fifty‐two fetuses were studied; 20 (38%) underwent neonatal intervention and 32 (62%) did not. The most common diagnosis was tetralogy of Fallot ( n  = 32). Fetuses with two ventricles that required an intervention had lower pulmonary valve diameter Z ‐score (PV‐Z‐score) (−4.8 ± 2.1 vs −2.6 ± 1.1; P  = 0.0002) and lower pulmonary valve to aortic valve annular diameter ratio (PV/AoV) (0.53 ± 0.15 vs 0.66 ± 0.1; P  = 0.003). Using a PV/AoV ratio of < 0.6 or a PV‐Z‐score of < −3 at final echocardiographic examination was highly sensitive (92%) but poorly specific (50%), whereas classifying direction of flow in the ductus arteriosus as either normal (all pulmonary‐to‐aorta) or abnormal (aorta‐to‐pulmonary or bidirectional) was both highly sensitive (100%) and specific (95%) for predicting the need for a neonatal intervention. Parameters for the single‐ventricle cohort did not reach statistical significance. Conclusions: Analysis of the pulmonary outflow tract and ductus arteriosus flow in the fetus with complex congenital heart disease can aid in identifying those that will require a neonatal intervention to augment pulmonary blood flow. This has important implications for the planning of delivery strategies.